Discovery in clinical and translational medicine - Diane C Wang; Xiangdong Wang (Clinical and Translational Discovery, 2021)
Abstract With the rapid development of biotechnologies and deep improvement of knowledge, “Discovery” is the initial period and source of innovation of clinical and translational medicine. The international journal of Clinical and Translational Discovery serves to highlight unknown or unclear aspects of clinical and translational medicine‐associated knowledge, technologies, mechanisms, and therapies (https://onlinelibrary.wiley.com/journal/27680622). The Discovery aims to define the interaction between genes, proteins, and cells, and explore molecular mechanisms of intercommunication and inter‐regulation. More discoveries of technologies and equipment are expected to improve method sensitivity, specificity, stability, analysis, and clinical significance. The first priority of Clinical and Translational Discovery is to turn gene‐, protein‐, drug‐, cell‐, and interaction‐based discoveries into health advancements. Clinical and Translational Discovery highly focuses on the discoveries of biological therapies and precision medicine‐based therapy elicited from computational chemistry, DNA libraries, target‐dependent small molecular drugs, high‐throughput screening, vaccination, immune therapy, cell implantations, gene editing, and RNA‐ or protein‐based inhibitors. Thus, Clinical and Translational Discovery sincerely welcome you to join and share the rapid development and future successes to come.